Employee Satisfaction on Green Building Practices in Apparel Industry - Weerathunga, E.D.V.N.; Weerakoon, K.G.P.K. (My University, 2017)
Energy efficiency was firstly commanded for commercial buildings in the world. However convincing all building owners about adopting sustainability measures has not been fully realised. Sustainable building owners benefits from reduced operating costs during building life cycle. Increased energy efficiency in the form of insulation, energy efficient light fittings, sophisticated Building Management Systems (BMS), microgeneration such as solar and wind turbines all result in measurable quantifiable reductions in operating costs for owners and tenants. Adoption of sustainable office building practises deliver increased employee productivity. This study aims to determine the satisfaction level of employees on green building practises. Employees being more satisfied with their work environment in green buildings compared with conventional ones. Employee satisfaction is an important consideration for operations to boost service quality and customer satisfaction. Increased productivity can leads to benefits such as financial savings resulting from reduced absenteeism, improved product quality, increased rates of production and increased sales. Green building designs and standards are developed to maintain the energy efficiency, and minimize energy and wastes.This study will allow property stakeholders, including government policy makers and investors/ developers to better understand the optimal type and level of sustainability to be incorporated in to the built environment. Key Words: Sustainable Building, Employee Satisfaction, LEED Certification